Surviving blind decomposition: A distributional analysis of the time-course of complex word recognition - Schmidtke, Daniel; Matkuki, K.; Kuperman, Victor (American Psychological Association, 2017)
The current study addresses a discrepancy in the psycholinguistic literature about the chronology of information processing during the visual recognition of morphologically complex words. Form-thenmeaning accounts of complex word recognition claim that morphemes are processed as units of form prior to any influence of their meanings, whereas form-and-meaning models posit that recognition of complex word forms involves the simultaneous access of morphological and semantic information. The study reported here addresses this theoretical discrepancy by applying a non-parametric distributional technique of survival analysis (Reingold & Sheridan, 2014) to two behavioural measures of complex word processing. Across seven experiments reported here, this technique is employed to estimate the point in time at which orthographic, morphological and semantic variables exert their earliest discernible influence on lexical decision reaction times and eye movement fixation durations. Contrary to form-then-meaning predictions, Experiments 1-4 reveal that surface frequency is the earliest lexical variable to exert a demonstrable influence on lexical decision reaction times for English and Dutch derived words (e.g., badness; bad + -ness), English pseudo-derived words (e.g., wander; wand + -er) and morphologically simple control words (e.g., ballad; ball + -ad). Furthermore, for derived word processing across lexical decision and eye-tracking paradigms (Experiments 1-2; 5-7), semantic effects emerge early in the time-course of word recognition, and their effects either precede or emerge simultaneously with morphological effects. These results are not consistent with the premises of the form-then-meaning view of complex word recognition, but are convergent with a form-and-meaning account of complex word recognition.
Keywords: Morphological processing; Survival analysis; Lexical decision; Semantics; Valence